Improvement of HER2I655V TARMS-PCR Performance by DNA Quality Analysis - Bugi Ratno Budiarto; Azamris Azamris; Desriani Desriani (ANNALES BOGORIENSES, 2017)
Reliable TARMS-PCR is a prerequisite in constructing a solid conclusion in genetic diagnostics. The validity of data generated by this molecular technique is hampered by a false positive result. In attempt to develop a  TARMS-PCR for HER2I655V genotyping with no interfering of bias we used DNase I to eliminate DNA contaminant resided in PCR reagent. TARMS-PCR without enzyme treatment using recombinant plasmids that contained HER2I655V gene with represented its alleles was used to evaluate the presence of false positive  result while DNase I treated-PCR reagent was used in TARMS-PCR to evaluate the effective dose of the enzyme and further to adjust the TARMS-PCR conditions.  PCR master mix kit used in this study produced a false positive result on HER2I655V TARMS-PCR as proven by the presence of multiple PCR products in Non-Template Control (NTC) and 0.1 U of the enzyme could eliminate this DNA contaminant effectively, although this pretreatment altered the specificity of HER2I655V TARMS-PCR genotyping on certain genotype. Combination of touchdown TARMS-PCR with another allele-specific primer recovered specificity of detection on this model system. Interestingly, this optimized HER2I655V TARMS-PCR can only be used for genotyping the clinical samples if only further optimization was done using genomic DNA as template